The link between regional temperature and regional incomes: Econometric evidence with sub-national data - Greßer, Christina; Meierrieks, Daniel; Stadelmann, David (Multiplicity in Decision-Making of Africa's Interacting Markets: The Functioning of Community Law, the Role of Market Participants and the Power of Regional Judges (MuDAIMa), 2021)
We study the link between temperature and economic development at the sub-national level, employing cross-sectional data from two distinct sources. In contrast to much of the existing cross-country literature on the temperature–income relationship, our setting allows for the inclusion of country-fixed effects.
Keywords: Natural disasters; Global warming; Sustainability; Disaster Management; Environmental Accounts; Environmental Accounting; Environmental Equity; Population Growth; Regional Economic Development; Regional Economic Change; Economic-Environmental Interactions; Trade; Environment; Climate Change; Econometric Evidence